Scrutinising internet banking security solutions - Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Anwar, Farhat; Mir, Roohie Naaz; Yaacob, Mashkuri (Inderscience Enterprises Ltd., 2020)
Internet-banking is a crucial service offered by financial Institutions and has gained popularity at a high pace. Owing to the increasing usage of this service, it is being frequently targeted by adversaries. The login process by the user is one of the main points that are at risk of this assault. Hence, a robust security mechanism is essential for warding off those risks. Among other security solutions, a typical arrangement presently employed is the one-time password (OTP), i.e., passwords that remain valid for a single exchange or session. However, the majority of these password generation and processing mechanisms do not fulfil the requirement of usability and/or scalability and hence can be considered as less reliable/fragile. This paper reviews the security mechanisms in E-banking. The pros and con of OTP as well as other non-OTP security solutions have been